Rubber Farmers Children’s Perceptions of Continuing Business between Generations: Case Study in Banyuasin Regency, South Sumatra - Dessy Adriani; Donna Septiani (Sawwa: Jurnal Studi Gender, 2023)
The declining interest of young people in farming extends beyond the food sector to include the plantation sector, warranting attention. This study addresses the insufficient exploration of the aspirations of plantation sector farmers’ children to pursue farming. The research focuses on analyzing the perceptions of farmers and their offspring regarding continuing rubber farming and identifying influencing factors in Ujung Tanjung Village, Banyuasin III District, Banyuasin Regency, South Sumatra. Employing a random sampling survey method, 36 school-age children were interviewed from a population of 175. Findings indicate that the children’s interest in rubber farming is relatively low (average score: 53.25), influenced by factors such as land area, participation in family farming, and agricultural extension. Although a generational transition in agricultural activities is observed in the village, guidance and counseling remain crucial to address farmer children’s perceptions.